2019
DOI: 10.1017/s1041610219000358
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine use among older adults with schizophrenia spectrum disorder: prevalence and associated factors in a multicenter study

Abstract: Objectives:Data on psychotropic medications of older patients with schizophrenia spectrum disorder are scarce. Specifically, information about the use of benzodiazepines among older patients with schizophrenia spectrum disorder is very limited. Because benzodiazepine use in older patients has been associated with many disabling side effects, its use in actual practice must be described and questioned. This study aimed at exploring the prevalence of benzodiazepine use and the clinical factors associated with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Cross‐sectional data were drawn from the CSA study, a cohort of 353 in‐ (34.1%) or outpatients (65.9%) aged 55 years or more with an International Classification of Diseases, 10th edition (ICD‐10) diagnosis of schizophrenia (82.4%) or schizoaffective disorder (17.6%). More detailed description of the study methodology can be found elsewhere 25–31 . Participants were recruited between February 2010 and June 2013 from 63 French state hospital psychiatric departments, each of them covering one mutually independent catchment area 32 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross‐sectional data were drawn from the CSA study, a cohort of 353 in‐ (34.1%) or outpatients (65.9%) aged 55 years or more with an International Classification of Diseases, 10th edition (ICD‐10) diagnosis of schizophrenia (82.4%) or schizoaffective disorder (17.6%). More detailed description of the study methodology can be found elsewhere 25–31 . Participants were recruited between February 2010 and June 2013 from 63 French state hospital psychiatric departments, each of them covering one mutually independent catchment area 32 .…”
Section: Methodsmentioning
confidence: 99%
“…In this report, we sought to examine potential differences between patients of similar age with LOS and NLOS as to sociodemographic and clinical characteristics of schizophrenia, comorbidity, psychotropic medications, quality of life, functioning, and mental health care utilization. To this purpose, we took advantage of the Cohort of older adults with Schizophrenia Aged 55 years or more (CSA) study, 25–30 a multicenter sample of 353 older adults with schizophrenia or schizoaffective disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, none of these trials were conducted in the elderly. Therefore, this poorly developed evidence base cannot explain or justify the widespread use of benzodiazepines in older patients with schizophrenia reported by Schuster et al (2019). This is especially true when the weak evidence for efficacy is considered in the context of the many adverse consequences of benzodiazepine use in younger and older patients.…”
mentioning
confidence: 99%
“…In this issue, a paper by Schuster et al (2019) explores an important aspect of the pharmacological treatment of older patients with schizophrenia or schizoaffective disorder the use of benzodiazepines. The authors describe 353 participants from 63 clinical centers across France in the "Cohort of Individuals with Schizophrenia Aged 55 Years or More."…”
mentioning
confidence: 99%
“…Smeets-Janssen et al (2020) have reported that in older schizophrenia patients, early-and late-onset ages form a continuum, with data showing one normally distributed population. Schuster et al (2020) have revealed that benzodiazepine use among OAS spectrum disorder is associated with medical comorbidities as well as cognitive and social functioning impairments. All these studies and many others highlight the intertwined nature of mental and physical health in schizophrenia, and the study by Cohen et al (2019) bears further testimony to that.…”
mentioning
confidence: 99%